Lateral retroperitoneal transpsoas approach to the lumbar spine for the treatment of spondylodiscitis. Issue 5 (October 2014) - Shepard, Matthew; Safain, Mina; Burke, Shane M.; Hwang, Steven; Kryzanski, James; Riesenburger, Ron I.
Abstract Spondylodiscitis is an infection of the intervertebral disc and adjacent vertebrae. With the advent of minimally invasive spinal surgery, less invasive approaches have been considered for the treatment of discitis. To date, however, there have been no reported cases of a minimally invasive lateral retroperitoneal transpsoas approach for the treatment of spondylodiscitis. The authors report a case of medically refractory discitis in a patient with multiple comorbidities who underwent a successful limited debridement via a lateral transpsoas corridor. This case describes a minimally invasive approach used to treat a patient with lumbar discitis/osteomyelitis who was otherwise a suboptimal surgical candidate.